A 3D Nanoporous Ni–Mo Electrocatalyst with Negligible Overpotential for Alkaline Hydrogen Evolution. Issue 7 (24th June 2014) - Wang, Yuhang; Zhang, Guoxin; Xu, Wenwen; Wan, Pengbo; Lu, Zhiyi; Li, Yaping; Sun, Xiaoming
Abstract 3D Ni–Mo electrocatalysts with well‐controlled composition, dimensions and nanoporosity are fabricated using a facile and effective electrodeposition technique on Cu foam. These catalysts exhibit enhanced stability and activity for the hydrogen evolution reaction (HER). By optimizing the Ni/Mo ratio, electrodeposition current density, and reaction time, the overpotential for the HER is reduced to 10 mV. The ultrahigh activity and stability of these catalysts are the highest among non‐precious‐metal electrocatalysts previously reported. The optimized Ni–Mo electrocatalyst has similar overpotential and a much higher current density compared to Pt/C. The improved HER performance is attributed to the Ni/Mo ratio (4:1), the large surface area, and the in situ growth method, which provides a well‐defined catalyst. These catalysts are potentially an attractive alternative to Pt in HERs, and therefore represent new technological opportunities for the development of renewable and economic hydrogen production.